1997
DOI: 10.1097/00003246-199704000-00005
|View full text |Cite
|
Sign up to set email alerts
|

A prospective, randomized, controlled evaluation of peripheral nerve stimulation versus standard clinical dosing of neuromuscular blocking agents in critically ill patients

Abstract: Use of peripheral nerve stimulation for monitoring the degree of blockade and adjusting drug doses in continuously paralyzed critically ill medical patients results in lower doses of vecuronium to maintain a desired depth of paralysis, and allows a faster recovery of neuromuscular function and spontaneous ventilation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0
2

Year Published

1997
1997
2016
2016

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 120 publications
(42 citation statements)
references
References 43 publications
0
40
0
2
Order By: Relevance
“…Studies that have compared TOF-guided NMBA titration to titration based on subjective clinical assessments in patients with mixed indications for paralysis have yielded disparate results. Rudis et al 26 reported that lower doses of NMBAs were used and recovery from paralytic agents was faster in patients randomized to TOF-guided therapy, whereas 2 other studies 27,28 showed no difference between groups in total paralysis time, recovery time, and amount of drug used. In a randomized controlled trial 29 of 102 patients with ARDS who were given cisatracurium, Figure 4 Degree to which baseline factors or concurrent therapies are perceived to alter the risk profile of neuromuscular blocking agents.…”
Section: Discussionmentioning
confidence: 99%
“…Studies that have compared TOF-guided NMBA titration to titration based on subjective clinical assessments in patients with mixed indications for paralysis have yielded disparate results. Rudis et al 26 reported that lower doses of NMBAs were used and recovery from paralytic agents was faster in patients randomized to TOF-guided therapy, whereas 2 other studies 27,28 showed no difference between groups in total paralysis time, recovery time, and amount of drug used. In a randomized controlled trial 29 of 102 patients with ARDS who were given cisatracurium, Figure 4 Degree to which baseline factors or concurrent therapies are perceived to alter the risk profile of neuromuscular blocking agents.…”
Section: Discussionmentioning
confidence: 99%
“…11,12,[21][22][23] Small, single-institution, prospective studies 1,22,23 suggest that the rates vary between 3.4% and 15.5%. Watling et al 17 reported a survey of the use of sedatives, analgesics, and NMB in the United States.…”
Section: Discussionmentioning
confidence: 99%
“…This search identified 38 articles and only English-language articles were reviewed to determine the original studies that evaluated pharmacist interventions on patient outcomes: four were clinical, ten economic, and zero humanistic. In addition to the clinical outcomes studies identified by our search, other relevant articles are discussed [3, 23,24]. This paper discusses the enhancement of outcomes by providing clinical pharmacy services to the critically ill in North America.…”
Section: Introductionmentioning
confidence: 99%